Differential expression and alternative splicing analyses of multiple tissues reveal albinism-associated genes in the Wels catfish (Silurus glanis) - Ozerov, M. Y. (Elsevier Inc., 2025)
Albinism is a widespread departure from a typical body colouration due to altered melanin production. The Wels catfish (Silurus glanis) is among the largest freshwater fish species in the world, and albino individuals occur both in the wild and in aquaculture. Here, we performed transcriptome-wide analysis of albino and normally pigmented S. glanis using four tissues (skin, dorsal fin, whole eye and liver) to identify genes associated with albinism by exploring patterns of differential expression (DE) and differential alternative splicing (DAS). Multi-tissue analyses revealed a large number of genes in skin (n = 1355) and fin (n = 614) tissue associated with the albino phenotype in S. glanis, while the number of DE genes in eye and liver tissues was lower (n = 188, n = 189, respectively). Several DE genes across multiple tissues were detected as the most promising candidates (e.g., hsp4, hsp90b1, raph1, uqcrfs1, adcy-family and wnt-family) potentially causally linked to the albino phenotype in Wels catfish. Moreover, our findings supported earlier observations of physiological differences between albino and normally pigmented individuals, particularly in energy metabolism and immune response. In contrast, there were only a few pigmentation-related genes observed among DAS genes (4 in skin, 2 in fin), the overlap between DAS and DE genes was low (n = 25) and did not include known pigmentation-related genes. This suggests that DAS and DE in Wels catfish are, to a large extent, independent processes, and the observed alternative splicing cases are probably not causally linked with albinism in S. glanis. This work provides the first transcriptome-wide multi-tissue insights into the albinism of Wels catfish and serves as a valuable resource for further understanding the genetic mechanisms of pigmentation in fish. © 2023